IgGFc-binding protein and MUC2 mucin produced by colonic goblet-like cells spatially interact non-covalently and regulate wound healing - Gorman, Hayley; Moreau, France; Dufour, Antoine; Chadee, Kris (Frontiers in Immunology, 2023)
The colonic mucus bilayer is the first line of innate host defense while at the same time house and nourish the commensal microbiota. The major components of mucus secreted by goblet cells are MUC2 mucin and the mucus associated protein, FCGBP (IgGFc-binding protein). In this study, we determine if FCGBP and MUC2 mucin were biosynthesized and interacted together to spatially enhanced the structural integrity of secreted mucus and its role in epithelial barrier function. MUC2 and FCGBP were coordinately regulated temporally in goblet cells and in response to a mucus secretagogue but not in CRISPR-Cas9 gene edited MUC2 KO cells. Whereas ~85% MUC2 was colocalized with FCGBP in mucin granules, ~50% of FCGBP was diffusely distributed in the cytoplasm of goblet cells. STRING-db v11 analysis of the mucin granule proteome revealed no protein-protein interaction between MUC2 and FCGBP however, FCGBP interacted with other mucus associated proteins. FCGBP and MUC2 interacted via N-linked glycans and were non-covalently bound in secreted mucus with cleaved low molecular weight FCGBP fragments. In MUC2 KO, cytoplasmic FCGBP was significantly increased and diffusely distributed in wounded cells that healed by enhanced proliferation and migration within 2 days whereas, in WT cells, MUC2 and FCGBP were highly polarized to the wound margin that impeded wound closure by 6 days. In DSS colitis, restitution and healed lesions in Muc2+/+ but not Muc2-/- littermates, was accompanied by a rapid increase in Fcgbp mRNA and delayed protein expression at 12- and 15-days post DSS, implicating a potential novel endogenous protective role for FCGBP in wound healing to maintain epithelial barrier function.